O Janie Żdżarowskim i jego znaku notarialnym użytym w nietypowej funkcji ekslibrisu - Jakub, Łukaszewski (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
Ekslibris przypisywany w literaturze Wojciechowi Strzałkowskiemu, najstarszy tego rodzaju polski księgoznak odbijany za pomocą klocka drzeworytniczego na kartach książkowych, rzeczywiście należał do Jana Żdżarowskiego. Pierwotnie Żdżarowski używał klocka do wykonywania znaku notarialnego — to najstarszy taki przypadek z terenów Polski. Narzędzie wykonano około 1517–1518 roku, na pewno przed 26 stycznia 1519 roku.
On Jan Żdżarowski and his notarial sign used untypically as bookplate
The oldest Polish bookplate known today and imprinted directly from a woodcut block on book pages is one attributed to Wojciech Strzałkowski, a notary from Gniezno (dated to 1519–1520). It can be found in an incunabulum from the collection of the Cathedral Library in the Archdiocesan Archives in Gniezno (Formularium instrumentorum ad usum Curiae Romanae [Hagenau: Heinrich Gran, before 17 August 1492], in 4o, no. Inc. 37). In the article the author demonstrates that the sign in fact belonged to Jan Żdżarowski (–1551), a public notary as well as canon of Poznań, Włocławek and Kraków. In his notarial admission (of 26 January 1519) Żdżarowski used a woodcut block to make his notarial sign (at that time notaries usually drew their signs). He used the same block to make a bookplate. An analysis of the state of preservation of both prints demonstrates that the block used to make them originated around 1517–1518, certainly before 26 January 1519, perhaps in Kraków. This is the oldest known case of a block being used to make a notarial sign by a notary from Poland and, at the same time, the first case of the same tool being used also to make a bookplate. The annex features an edition of the text of Jan Żdżarowski’s admission.
Keywords: Jan Żdżarowski; notarial sign; bookplate; woodcut block; early printed books; incunabula; Wojciech Strzałkowski; znak notarialny; klocek drzeworytniczy; ekslibris